2012
DOI: 10.1371/journal.pone.0038673
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Retinal Pigment Epithelium (RPE)

Abstract: BackgroundAge-related changes in the retina are often accompanied by visual impairment but their mechanistic details remain poorly understood.MethodologyProteomic studies were pursued toward a better molecular understanding of retinal pigment epithelium (RPE) aging mechanisms. RPE cells were isolated from young adults (3–4 month-old) and old (24–25 month-old) F344BN rats, and separated into subcellular fractions containing apical microvilli (MV) and RPE cell bodies (CB) lacking their apical microvilli. Protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 32 publications
3
56
0
1
Order By: Relevance
“…We also reported immunolocalization of DJ-1 protein in both young and aged rat RPE cells [7]. Here we extend our initial observations of DJ-1 expression and further discuss DJ-1 function in the RPE cells.…”
Section: 1 Introductionsupporting
confidence: 85%
“…We also reported immunolocalization of DJ-1 protein in both young and aged rat RPE cells [7]. Here we extend our initial observations of DJ-1 expression and further discuss DJ-1 function in the RPE cells.…”
Section: 1 Introductionsupporting
confidence: 85%
“…Exposure to reactive oxygen species may affect the health of photoreceptors and the Bruch’s membrane [24]. RPE isolated from young and old rats share only ~50% of their protein expression and the differences concern mostly proteins involved in pathways of oxidative stress such as catalase, glutathione peroxidase, and superoxidate dismutase [25]. Chen et al found that exposure to oxidized photoreceptor outer segments induced the multinucleation process in the RPE cells [23], and that age-related RPE multinucleation was more profound in central retina.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies used included PARK7 (TA301239, Origene, Rockville, MD, 1:750), red/green opsin (AB5405, Millipore, Billerica, MA, 1:200), ribeye (CtBP2, 612044, BD Transduction, 1:500), ezrin (MS-661-P0, Thermo Scientific, Rockford, IL, 1:100), tyrosine hydroxylase (TH) (MAB318, Millipore, 1:400), 8-oxoguanine (MAB3560, Millipore, 1:300), and Nrf2 (sc-13032, Santa Cruz Biotechnology, Santa Cruz, CA, 1:100). For DJ-1 staining, sections were processed and labeled as previously described (Gu et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…We initially reported the identification of DJ-1 peptides in both young and aged retinal pigment epithelium (RPE) lysates using a proteomic approach (Gu et al, 2012). Further studies showed that DJ-1 expression is higher in older eyes, suggesting a correlation between DJ-1 levels of expression and oxidative stress in the retina.…”
Section: Introductionmentioning
confidence: 99%